Good Corporate Governance: Does The Timeliness of Financial Reporting Has an Effect to The Investors’ Reaction? - Reni Furwanti; Slamet Haryono; Dini Maulana Lestari (P3M Politeknik Negeri Bali, 2021)
This research aims to find out the influence of independent committee boards, audit committee repats, foreign ownership, and audit quality on the timeliness of financial reporting and their impact on investors' reactions both directly and indirectly. This research uses a quantitative method with population and sample of companies registered in Jakarta Islamic Index (JII). Data will be processed using path analysis using IMB SPSS Statistic 22 software. Based on the results of this research, it is known that directly, independent commissioner variables and audit quality have a positive effect on investor reactions, while foreign ownership variables and audit committee meetings have a negative effect on investors’ reactions. While the indirect influence can be known that only audit committee meetings, foreign ownership, and audit quality can have a significant impact on investors' reactions through the timeliness of disclosure of financial statements as intervening variables. The implication of this research is to prove that the existence of corporate governance in terms of determining the intensity of audit committee meetings, foreign ownership, and determination of KAP selection in improving the quality of audits can make the company more efficient and timely in disclosing its financial statements in order make positive reactions from investors that indicates good news for the company.